2012
DOI: 10.1080/10473289.2012.654896
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly eliminating pathogenic microorganisms in large air space using spraying •OH radicals

Abstract: A new method for rapidly eliminating pathogenic microorganisms in large air space using spraying *OH radicals is presented in this paper With a physical method of strong electric-field discharge, large numbers of *OH radicals were produced by the oxygen activated particles of O2+, O(1D), O(3P), etc., and the introducing reagent HO2-. The gram-positive bacteria Bacillus subtilis, the gram-negative bacteria Serratia marcescens, and Bacillus spores were used for the eliminating experiments. Results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Thus, ROS supports cell damage in oxidative stress, which might be repaired via the antioxidant process in microbial cells, where in, microbes might inactivate ROS radicals and destruct healthy cells. 81 Such ROS collapse different polypeptide chains of proteins by charge modification, resulting in structural modification of amino acids which inhibit the activity of protein due to less active site.…”
Section: Discussion and Types Of Semiconductor Photocatalystsmentioning
confidence: 99%
“…Thus, ROS supports cell damage in oxidative stress, which might be repaired via the antioxidant process in microbial cells, where in, microbes might inactivate ROS radicals and destruct healthy cells. 81 Such ROS collapse different polypeptide chains of proteins by charge modification, resulting in structural modification of amino acids which inhibit the activity of protein due to less active site.…”
Section: Discussion and Types Of Semiconductor Photocatalystsmentioning
confidence: 99%
“…Detailed information on the concentration of important VOCs in the indoor environment and their exposure limits according to indoor air quality (IAQ) guidelines of different organizations are available in the review by Shrubsole et al [ 67 ]. Nearly all organic compounds present in indoor air can undergo photocatalytic oxidation in the presence of highly reactive species [ 68 ]. The hydroxyl (·OH) radical, also known as “mother nature’s vacuum cleaner" [ 69 ], is a highly reactive compound that can be employed in an HVAC system to readily decompose VOCs to provide clean air for the occupants.…”
Section: Essential Anti-pandemic Components For Post-covid-19 Hvac Sy...mentioning
confidence: 99%
“…Several studies have demonstrated the potential of employing •OH radicals for indoor air quality management 68 , 75 , 76 . Sarwar et al [ 77 ] proposed an indoor air quality model to estimate the concentration of •OH radicals in indoor air by simulating indoor homogeneous reactions.…”
Section: Essential Anti-pandemic Components For Post-covid-19 Hvac Sy...mentioning
confidence: 99%
“…Several other air purifying methods were also reported in the recent past. For example, ·OH Fog-drops based on an electric-field discharge plasma, which can kill microorganisms in air quickly [14] , [15] , [16] ; Ultra violet (UV) technology based of air sterilization [17] ; Air rapid heating rapid cooling sterilization [18] …etc. Useful information on such methods can be found in a review paper by Choi et al in 2021 [19] .…”
Section: Hardware In Contextmentioning
confidence: 99%